(3CYeGd eDJeQ GdTQGcI Hjf GdbWGY GdYGe hGdbWGY GdNGU (B:s (3ebGQHI GbJUGOjI, bGfhfjI hejOGfjI (B/s ((3HjQhJ(B: s (3GdLeYjI GddHfGfjI dadSaI GdbGfhf(B, s, 2013)
(3GdYhdeI hCNdGbjGJ GdCYeGd(B- (3GdNUNUI Hjf GdfXQjI hGdJWHjbI(B- (3GdTQGcI aj GdbGfhf GdGQhHj(B- (3GdeaGVdI Hjf GdbWGY GdYGe hGdNGU(B- (3GdYdGbI GdLOdjI Hjf GdbWGY GdYGe hGdbWGY GdNGU(B- (3TQGcI GdYGe hGdNGU(B- (3JWhjQ GdCOGA GdGcGOjej hGdHMK GdYdej(B- (3OhQ GdTQcGJ GdeJYOOI GdLfSjGJ aj GdJGKjQ Ydi SjGOI GdOhd(B- (3Mhd GdTQGcI Hjf GdbWGY GdYGe hGdNGUs
Keywords: (3GdbWGY GdNGUs; (3GdbWGY GdYGes; (3eDJeQGJs